Exploring linkages: addressing the relationship between the climate crisis and HIV prevention with recommendations for emerging pre-exposure prophylaxis programs - Williams, Katie M.; Olisa, Adaobi Lisa; Wilcher, Rose (Frontiers in Reproductive Health, 2024)
Short-and long-term impacts of the climate crisis continue to be felt across the public health landscape. Many individuals marginalized by the climate crisis also navigate a higher likelihood of exposure to HIV. By understanding this relationship, we can better position HIV prevention, and preexposure prophylaxis (PrEP) programs specifically, to meet user needs in communities experiencing the effects of the climate crisis. In support, we propose four recommendations for mitigating the impact of the climate crisis on those who may benefit from PrEP: 1) leverage existing and emerging research and lived experience to intentionally target and appropriately reach individuals affected by the climate crisis who may need or want PrEP; 2) emphasize the need for more climate-resilient PrEP products within the research and development pipeline; 3) build a continued understanding of the role of the climate crisis-HIV relationship in product introduction through national collaboration; and 4) strengthen the integration of PrEP service delivery and response to intimate partner violence. The PrEP market is set for rapid expansion with the introduction of new prevention methods to enable choice. To be comprehensively responsive to potential PrEP users, we must consider and address how the climate crisis changes not only the environmental landscape, but the prevention ecosystem.